Involvement of humic acid in production and physiology of soybean (Glycine max L.) under drought stress conditions - Budiyanto, Susilo; Almas, Hanifah Syifaa; Rosyida, Rosyida (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: This study aims to determine the best effect of soybean plant production and physiology on humic acid application under drought-stress conditions. Methods: This study used a factorial complete randomized design with three levels of humic acid (0 ppm, 500 ppm, and 1000 ppm) and three levels of drought stress (80% KL, 60% KL, and 40%). The parameters analyzed were the number of flowers, pod fresh weight, pod dry weight, number of seeds, leaf chlorophyll, relative water content (RWC), and stomatal density. Results: The highest number of flowers was in the 80% KL drought stress treatment; the highest pod fresh weight and pod dry weight were in the 80% KL drought stress treatment; the highest number of seeds was in the 80% KL drought stress treatment; the highest leaf chlorophyll was in the 1000 ppm humic acid treatment and 80% KL drought stress; the highest relative water content (RWC) was in the interaction between 1000 ppm humic acid and 80% KL drought stress; and the highest stomatal density was in the 80% KL drought stress treatment. Conclusion: Humic acid application affects leaf chlorophyll and relative water content (RWC). Drought stress affects the number of flowers, pod fresh weight, pod dry weight, number of seeds, leaf chlorophyll, relative water content (RWC), and stomatal density. There was an interaction effect between humic acid application and drought stress on the relative water content (RWC) parameter.